Pengaruh Switching Cost sebagai Pemoderasi Hubungan antara Kepuasan dan Loyalitas Konsumen - Aditya Putranto Ardhani (Fakultas Bisnis UKDW, 2007)
The aim of this research is to exornine the moderating effect of switching cost on the relationship between customer satisfaction